CORONA VIRUS: A STATE-OF-ART - Dr. Anamika Ahirwar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The latest plague of COVID-19, with the deaths of thousands of people, has taken the world to an unprecedented idle with a huge and economic burden and a crippling medical penalty. Despite some successes in mitigation, prevention and suppression strategies, the regions have generally had insufficient economic and health outcomes. Artificial intelligence from data analysis and understanding to diagnostic therapy and performance in all aspects of this crisis should be used. Medical, toxicological and genomic data can be gathered, structured and analysed using artificial intelligence.